Alkyl vs. aryl modifications: a comparative study on modular modifications of triphenylphosphonium mitochondrial vectors. Issue 6 (7th September 2021) - Ong, How Chee; Coimbra, João T. S.; Kwek, Germain; Ramos, Maria J.; Xing, Bengang; Fernandes, Pedro A.; García, Felipe
Abstract : Alkyl chain extension and aryl methylation can be employed to enhance mitochondrial uptake in triphenylphosphonium vectors. Here we compare these complementary strategies and their mitochondrial-targeting effects using a modular synthetic approach. Abstract : Triphenylphosphonium (TPP + ) moieties are commonly conjugated to drug molecules to confer mitochondrial selectivity due to their positive charge and high lipophilicity. Although optimisation of lipophilicity can be achieved by modifying the length of the alkyl linkers between the TPP + moiety and the drug molecule, it is not always possible. While methylation of the TPP + moiety is a viable alternative to increase lipophilicity and mitochondrial accumulation, there are no studies comparing these two separate modular approaches. Thus, we have systematically designed, synthesised and tested a range of TPP + molecules with varying alkyl chain lengths and degree of aryl methylation to compare the two modular methodologies for modulating lipophilicity. The ability of aryl/alkyl modified TPP + to deliver cargo to the mitochondria was also evaluated by confocal imaging with a TPP + -conjugated fluorescein-based fluorophore. Furthermore, we have employed molecular dynamics simulations to understand the translocation of these molecules through biological membrane model systems. These results provide further insights into the thermodynamics of this process and the effect of alkyl and aryl modular modifications.